2016
DOI: 10.1038/ncomms12749
|View full text |Cite
|
Sign up to set email alerts
|

Continuous injection synthesis of indium arsenide quantum dots emissive in the short-wavelength infrared

Abstract: With the emergence of applications based on short-wavelength infrared light, indium arsenide quantum dots are promising candidates to address existing shortcomings of other infrared-emissive nanomaterials. However, III–V quantum dots have historically struggled to match the high-quality optical properties of II–VI quantum dots. Here we present an extensive investigation of the kinetics that govern indium arsenide nanocrystal growth. Based on these insights, we design a synthesis of large indium arsenide quantu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
298
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(314 citation statements)
references
References 50 publications
15
298
1
Order By: Relevance
“…Over the last decades, the optical tissue transparency window in NIR‐I has been employed for noninvasive optical bioimaging of small animals in biomedical research , advancing the development of imaging guided phototherapy and drug delivery . Quite recently, in addition to the conventional NIR‐I window, two or more optical windows have been identified, namely NIR‐II (~1000‐1350 nm) and NIR‐III or short‐wave IR (SWIR) (~1550‐1870 nm) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decades, the optical tissue transparency window in NIR‐I has been employed for noninvasive optical bioimaging of small animals in biomedical research , advancing the development of imaging guided phototherapy and drug delivery . Quite recently, in addition to the conventional NIR‐I window, two or more optical windows have been identified, namely NIR‐II (~1000‐1350 nm) and NIR‐III or short‐wave IR (SWIR) (~1550‐1870 nm) .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, NIR‐I and NIR‐II windows have been shown to be suitable for the through‐skull brain imaging in vivo . Moreover, few recent studies have found that light in SWIR (or NIR‐III) window has even better tissue permeability , that makes it advantageous for the imaging utilizing exogenous and endogenous agents .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the quantum yield, functionality, and biocompatibility of SWIR fluorophores is an active focus of emerging research studies (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Significancementioning
confidence: 99%
“…Other D-A-D structured systems and www.advancedsciencenews.com www.advtherap.com [59] SWCNTs-cholate 808/900-1500 0.4 Intravital tumor vessels imaging RGD peptide [5] Chiral SWCNTs 725/850-1350 -Vascular imaging Non-specific [60] QDs Ag 2 S-6PEG 808/1200 15.5 4T1 tumor xenograft imaging, lymphatic drainage, imaging, angiogenesis imaging, brain tumor surgery Non-specific [14,36,38] Ag 2 S-DSPE-PEG 808/1100 -Tumor vessel imaging, image-guided drug delivery cRGD, Ald [45,46] Ag 2 S@SiO 2 785/1135 22.7 NIR-II tumor imaging cRGDfK-R6G peptide [61] InAs-CdSe-CdS 785/1080 16 Non-invasive through-skull fluorescence imaging of the brain vasculature of murine models Non-specific [62] PA-NIRQD 910/1200 >10 Colon cancer imaging MMP-2 activation [43] RENPs Imaging of blood vasculature in the mouse brain and hindlimb Non-specific [29] Organic fluorophores CH1055 980/1055 0.3 Imaging of lymphatic vasculature, orthotopic glioblastoma and brain tumor, and guiding surgery Several major aspects need more attention.…”
Section: Conclusion and Perspectivementioning
confidence: 99%